PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KADER TBC YANG DIMEDIASI OLEH MOTIVASI KERJA PADA DINAS KESEHATAN KABUPATEN DELI SERDANG - Lubis, Agus Hendra; Sabrina, R; Efffendy, Sjahril (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
The study examines the impact of leadership and compensation on the performance of tuberculosis (TBC) cadres, with work motivation serving as a mediating factor. It employs a descriptive survey research design with a quantitative approach, involving 64 respondents from the Deli Serdang District Health Office. Data were collected through interviews and questionnaires and analyzed using Partial Least Square (SmartPLS) to test seven hypotheses. The findings reveal that leadership and compensation both have a positive and significant effect on performance and motivation. Additionally, work motivation significantly mediates the relationship between leadership, compensation, and performance, indicating that motivation strengthens the impact of leadership and compensation on cadre performance.